Spatial and seasonal variations in atmospheric aerosols over Nigeria: Assessment of influence of intertropical discontinuity movement. (January 2019) - Ayanlade, Ayansina; Atai, Godwin; Jegede, Margaret Olusolape
This study examines the influence of intertropical discontinuity movement on seasonality and distribution of atmospheric aerosols over Nigeria, using remote sensing approach. The Moderate Resolution Imaging Spectroradiometer (MODIS) Terra aerosol optical depth, wind speed and precipitation/intertropical discontinuity (ITD) dataset were used. Geospatial interpolation model was used to analyse the aerosol seasonal distribution. Correlations analysis was used to evaluate the degree of influence of wind and ITD on the monthly distribution of aerosol. The results show significant variations in monthly mean distributions of aerosol, but the variation is much more extraordinary during Harmattan season than Wet and Dry seasons, with 0.29 ⩽ aerosol optical depth ⩾ 0.46. In other ecological zones, the highest mean aerosol optical depth values were observed in the months of December, January and February with 0.30 ⩽ aerosol optical depth ⩾ 0.60, with highest value in Sahel ecological zone. Generally, the results further show a strong relationship between aerosol optical depth distribution and migration of ITD with correlation r 2  ⩾ 0.60 @ p  = 0.05 mostly during Dry and Harmattan seasons but relatively low correlation r 2  ⩽ 0.40 @ p  = 0.05 during Wet season. The major findings of this study are that seasonal shifts in the location of the ITD considerably affect not only rainfall distribution, resulting in the Wet and Dry seasons in the study area, but also have significant impacts on atmospheric aerosol distributions. Although not all aerosols presented in this study are dust originated from Sahara desert, since biomass-burning activities frequently occur in the study area, the study concludes that satellite-based aerosol optical depth datasets continue to be advantageous to understand atmospheric aerosols distribution in a region where there is fewer ground aerosols data.